(untitled) - Hennessy, John J. (San Francisco, California, 1996)
Computer Architecture: A Quantitative Approach was the first book to focus on computer architecture as a modern science. Its publication in 1990 inspired a new approach to studying and understanding computer design. Now, the second edition explores the next generation of architectures and design techniques with view to the future.
Kiến trúc máy tính
Keywords: Computer architecture,Kiến trúc máy tính